Phosphorus and Nutrition in Chronic Kidney Disease - Emilio González-Parra; Carolina Gracia-Iguacel; Jesús Egido; Alberto Ortiz (International Journal of Nephrology)
Patients with renal impairment progressively lose the ability to excrete phosphorus. Decreased glomerular filtration of phosphorus is initially compensated by decreased tubular reabsorption, regulated by PTH and FGF23, maintaining normal serum phosphorus concentrations. There is a close relationship between protein and phosphorus intake. In chronic renal disease, a low dietary protein content slows the progression of kidney disease, especially in patients with proteinuria and decreases the supply of phosphorus, which has been directly related with progression of kidney disease and with patient survival. However, not all animal proteins and vegetables have the same proportion of phosphorus in their composition. Adequate labeling of food requires showing the phosphorus-to-protein ratio. The diet in patients with advanced-stage CKD has been controversial, because a diet with too low protein content can favor malnutrition and increase morbidity and mortality. Phosphorus binders lower serum phosphorus and also FGF23 levels, without decreasing diet protein content. But the interaction between intestinal dysbacteriosis in dialysis patients, phosphate binder efficacy, and patient tolerance to the binder could reduce their efficiency.